2016
DOI: 10.1186/s13058-016-0745-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicted 25-hydroxyvitamin D in relation to incidence of breast cancer in a large cohort of African American women

Abstract: BackgroundVitamin D deficiency, which has been linked to an increased risk of colorectal cancer, is particularly common among African Americans. Previous studies of vitamin D status and breast cancer risk, mostly conducted in white women, have had conflicting results. We examined the relationship between predicted vitamin D status and incidence of breast cancer in a cohort of 59,000 African American women.MethodsParticipants in the Black Women’s Health Study have been followed by biennial mail questionnaires s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 63 publications
3
43
0
Order By: Relevance
“…Their study also identified that serum 25OHD levels were independently associated with breast cancer prognosis in premenopausal women. While some studies failed to show this relationship [ 44 , 48 , 49 ]. The classification of ER status and/or assessment of 25(OH)D3 level (dietary, supplement taken and the time of blood samples collection etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Their study also identified that serum 25OHD levels were independently associated with breast cancer prognosis in premenopausal women. While some studies failed to show this relationship [ 44 , 48 , 49 ]. The classification of ER status and/or assessment of 25(OH)D3 level (dietary, supplement taken and the time of blood samples collection etc.)…”
Section: Discussionmentioning
confidence: 99%
“…They found that elevations in serum 25(OH)D concentrations were associated with superior overall survival especially among premenopausal women 37 , strongly suggesting the use of serum vitamin D level as a prognostic marker for breast cancer. Moreover, among African American women, data showed that vitamin D deficiency increased breast cancer susceptibility by approximately 23% 38 , indicating vitamin D intake could be consider as a preventive factor for breast cancer incidence.…”
Section: Potentiating Vitamin D As An Anticancer Agentmentioning
confidence: 99%
“…There is evidence that breast cancer risk among black women is affected by 25(OH) D concentrations. For example, a prospective study from the Black Women's Health Study found that the incidence rate ratio for invasive breast cancer for lowest vs. highest quartile of predicted 25(OH) D was 1.23 (95% CI, 1.04, 1.46) [3]. For another study, see Ref.…”
Section: William B Grantmentioning
confidence: 99%
“…The proposed mechanisms whereby vitamin D metabolites reduce the risk of breast, colorectal, prostate, and overall cancer include surveillance of cells, reduced angiogenesis around tumors, and antimetastasis actions (see references in [3,4]). However, higher 25(OH) D concentrations have also been found associated with increased risk of colorectal and prostate cancer [4].…”
Section: William B Grantmentioning
confidence: 99%